Avaliação da idade auditiva em crianças usuárias de implante coclear - Pollyanne de Paula Ferreira Bastos (2020)
Introduction: Speech therapy assessment of children using cochlear implants is extremely important to monitor issues related to hearing and language development. The application of instruments through questionnaires, aimed at parents, is a way of monitoring the development of these children. In this sense, the LittlEars instrument, translated and adapted to Brazilian Portuguese, aims to assess children's hearing development in the first 48 months after cochlear implantation. Objectives: To assess the hearing age of children using CI, based on the observation of parents, using the LittlEars instrument. Method: This study consisted of two stages: 1) 1 systematic literature review article entiled: The use of the LittlEars instrument: a systematic review and carried out through a systematic mapping and 2) cross-sectional observational study, data were collected after approval by the Ethics and Research Committee - COEP, under number CAAE 08326918.7.0000.5149 which sought, through the LittlEars instrument, to assess the hearing age of children up to 7 years old treated at HC / UFMG. The sample consisted of 20 parents of children using cochlear implants. First, anamnesis was performed, then the LittlEars questionnaire was applied. The collection took place at the Audiology Outpatient Clinic - HC / UFMG from March to July 2019. The data were analyzed using SPSS software, version 23.0. Descriptive analysis of the data was carried out, through the frequency distribution of categorical variables and analysis of measures of central tendency and dispersion of continuous variables. Fisher's exact test was used for association analyzes. For correlation analysis, Spearman's correlation coefficient was used, with p <= 0.05 being considered significant. Result: Step 1) In the systematic review on the use of LittlEars, snowballing was selected and performed for 24 studies. In total, 29 studies were identified, from 12 different countries, between the years 2005 and 2018 and peaked in 2014, covering the application of the LittlEars instrument. Step 2) Of the 20 children whose parents answered the questionnaire, 12 were girls and 08 boys, aged between 24 and 87 months (average of 58.65 months). The average implantation time after activation was 38.70 months. Of the 35 questions presented in the LittlEars questionnaire, questions 9 (Does your child respond with alarm (fright) when he hears an angry person's voice?), 14 (When your child is sad or in a bad mood, he can be calm or change his behavior in the presence of music?) and 20 (Does your child recognize the names of members of your family?), have an association, with statistical relevance, about the variables: time of IC use (up to 12 months or more), use of hearing aids after the diagnosis of hearing loss and age at CI activation. Conclusion: It is noteworthy that the LittlEars instrument can be easily applied to assess the auditory development of children using CI. In this study it was found that most children had a hearing age compatible with the time of CI use, however the results revealed that the age of implantation, the time of implant use and the use of hearing aids right after the diagnosis of hearing loss influence auditory development, especially in relation to auditory discrimination, speech perception and prosodic aspects of language.